A Constrained Multi-Item Inventory Model Under Probabilistic Demand Using Linear Programming Techniques - Hassan, Aisha Sheikh; Yahaya, Ahmed Abubakar; Usman, Abdullahi Mohammed; Sulaiman, Dauda (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
This study involves inventory management model to obtain ordering policy that maximizes profits of several items with constraints under probabilistic demand. The goal is to obtain an optimal EOQ, in order to maximize profit for each of the state of demand for the items. The decision to order more units of items or not to order additional units are given as the decision variables which are represented by zero (0) and one (1), these decisions are made at the beginning of each planning period using 2-period dynamic programming technique (DP). In order to handle the constraints given by the management, the Linear programming technique (LP) is used. The application of the model was demonstrated by a numerical illustration.